2019
DOI: 10.5688/ajpe6735
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Advanced Pharmacy Practice Experience Grading Scheme on Residency Match Rates

Abstract: Objective. To examine the effect of advanced pharmacy practice experience (APPE) grading schemes on residency match rates Methods. A cross-sectional survey was administered to United States schools of pharmacy to determine APPE grading scheme. Post-graduate year 1 residency match data for the years 2013-2015 was obtained from the American Society of Health-System Pharmacists. Additional variables thought to affect residency match rates were collected from publically available sources and prior research. Unadju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…A variety of other factors were associated with higher match rates in individual studies, including the age of the school, 25 accreditation status, 22 number of funded faculty, 23 class size, 24 and minority enrollment 24 . Use of a numeric grading scale (vs pass/fail grading) was associated with a higher match rate in one study 7 but not when advanced pharmacy practice experiences were studied exclusively 26 . One study demonstrated that candidates who applied during their graduation year were more likely to match than those who had been out of school for a year or longer 27…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of other factors were associated with higher match rates in individual studies, including the age of the school, 25 accreditation status, 22 number of funded faculty, 23 class size, 24 and minority enrollment 24 . Use of a numeric grading scale (vs pass/fail grading) was associated with a higher match rate in one study 7 but not when advanced pharmacy practice experiences were studied exclusively 26 . One study demonstrated that candidates who applied during their graduation year were more likely to match than those who had been out of school for a year or longer 27…”
Section: Resultsmentioning
confidence: 99%
“…Programs should even consider sharing the tools used to evaluate candidates, as doing so may help applicants self‐select the programs to which they are best suited (ie, reducing the number of applications requiring review). For example, if academic pedigree or other school‐related factors are important to an RPD (as some studies in this review suggested 7,22‐28 ), that should be explicitly stated so that candidates do not apply to programs (and pay additional fees in PhORCAS) if they will not even be considered.…”
Section: Discussionmentioning
confidence: 99%
“…This preference has been documented in other studies; however, one study's findings suggested that pass/fail grading had no impact on residency match rate. 13,18,30 Residency directors' preference for letter grades may be due to their perceived ability to use grades to differentiate between applicants. However, experiential education program directors at pharmacy schools may prefer that pass/fail grading be used for APPEs.…”
Section: Discussionmentioning
confidence: 99%
“…Which letter grade a passing point is equivalent, for example a C or a B, depends on the course director and/or school policy. Although there is no data on the use of a letter verses pass/fail grading system in pharmacy schools, the results of previous studies suggest that a letter grading system seems to be more commonly used in pharmacy schools the United States (Pick et al, 2013;Pincus et al, 2019). Given that a letter grading system seems to be more commonly used in didactic courses and it may take a long process to change the grading system, this study may provide an example of how to incorporate a criterion-referenced method to set Janani, Risla, Shanika et al Improving community pharmacists' ability to detect drug problems Pharmacy Education 20(1) 303 -312 standards for written tests in a didactic course with a letter grading system.…”
Section: Discussionmentioning
confidence: 99%
“…In pharmacy education in the United States, the type of grading systems used in didactic courses has not been formally reported; however, several sources suggest that a letter grading system (i.e., the A, B, C, D, and F grading system), instead of a pass/fail grading system, is more widely used. For example, in one survey administered to pharmacy schools and colleges in the United States, 66% of the schools responded that they utilised the letter grading system for Advanced Pharmacy Practice Experience courses (Pincus et al, 2019). In addition, more than half of directors of pharmacy residency programmes viewed pass/fail grades unfavourably (Pick et al, 2013).…”
Section: Introductionmentioning
confidence: 99%